1984
DOI: 10.1177/0148607184008006695
|View full text |Cite
|
Sign up to set email alerts
|

Selenium Depletion in Burn Patients

Abstract: Victims of major burns may be at risk for selenium (Se) depletion because increased postinjury nutrient needs are often met by total parental nutrition and tube feedings which contain little Se. This study compared Se status of 17 burn patients and 191 healthy control subjects. Se intake of burn patients was lower than the intake of control subjects when total parenteral nutrition or tube feedings were used as primary nutrient sources but was comparable to the control intake when burn patients consumed oral di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
15
0
1

Year Published

1992
1992
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(19 citation statements)
references
References 31 publications
3
15
0
1
Order By: Relevance
“…4 These results support those of similar investigations among adults with burn injuries [5][6][7][8][9] and imply that Se requirements during burn injury may be higher than expected.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…4 These results support those of similar investigations among adults with burn injuries [5][6][7][8][9] and imply that Se requirements during burn injury may be higher than expected.…”
Section: Discussionsupporting
confidence: 81%
“…4 It is well established that plasma Se and Gpx values decline among adults with burn injuries and that Se supplementation is necessary to replenish Se status. [5][6][7][8][9][10] Furthermore, it is also known that intravenous Se, as part of a trace element cocktail, is related to reduced infection rates and length of stay among adult patients with burns. 7,8,11 Although data among adults is plentiful, the incidence and significance of depressed plasma Se and Gpx among children with burn injuries remains ambiguous.…”
mentioning
confidence: 99%
“…27 As early changes of the selenium status are induced by burn injury in humans 28 and animals, 29 these trace elements must be kept in mind for the treatment of burned patients. In these patients, large cutaneous losses of selenium, copper, and zinc have been indeed documented.…”
Section: Discussionmentioning
confidence: 99%
“…[101][102][103][104] Berger et al consistently demonstrated in a series of well controlled trials that trace element supplementation reduces infectious complications in burn patients. Supplementation (IV) of copper 2.5-3.1 mg/day, selenium 315-380 μg/day, and zinc 26.2-31.4 mg/day for eight to 21 days resulted in a significant reduction in the number of infections.…”
Section: Micronutrientsmentioning
confidence: 99%